Management of hyperlipidaemia: guidelines of the British Hyperlipidaemia Association. Issue 811 (May 1993) - Betteridge, D. J.; Dodson, P. M.; Durrington, P. N.; Hughes, E. A.; Laker, M. F.; Nicholls, D. P.; Rees, J. A.; Seymour, C. A.; Thompson, G. R.; Winder, A. F.
Abstract : There is considerable evidence to suggest that the identification and treatment of dyslipidaemia will reduce the risk of premature CHD, i.e. before the age of 65. Diagnosis of the cause of raised plasma lipid levels will enable appropriate decisions to be taken with regard to management. The cornerstone of treatment is nutritional counselling and attention to other major risk factors for CHD, particularly smoking and hypertension. For a small percentage of patients with severe hyperlipidaemia drug therapy is indicated. Appropriate drug choices need to be made based on the particular lipid abnormality to be treated. In general those patients with clinical vascular disease are treated more aggressively than those where the aim is primary prevention. More research is needed to determine individual risk more precisely and to allow proper targeting of therapy. Genetic factors, qualitative changes in lipoproteins, lipoprotein (a), fibrinogen, and other coagulation and thrombotic factors are likely to be important in individual risk assessment. There is no doubt that more information is needed from prospective studies of lipid-lowering therapy in terms of risk benefit for affected individuals. Hopefully the major studies currently underway will fill some of the gaps in our knowledge. Until then aggressive therapy with drugs should be reserved for those at highest risk where the benefit is likely to be greatest.